Diverse Mechanisms of Protective Anti-Pneumococcal Antibodies - Gingerich, Aaron D.; Mousa, Jarrod J. (Frontiers in Cellular and Infection Microbiology, 2022)
The gram-positive bacterium Streptococcus pneumoniae is a leading cause of pneumonia, otitis media, septicemia, and meningitis in children and adults. Current prevention and treatment efforts are centered around pneumococcal conjugate vaccines (PCV) that target the bacterial capsule polysaccharide (CPS), as well as antibiotics for pathogen clearance. While these methods have been enormously effective at disease prevention and treatment, there has been an emergence of non-vaccine serotypes, termed serotype replacement, and increasing antibiotic resistance among these serotypes. To combat S. pneumoniae, the immune system must deploy an arsenal of antimicrobial functions. However, S. pneumoniae has evolved a repertoire of evasion techniques and is able to modulate the host immune system. Antibodies are a key component of pneumococcal immunity, targeting both the CPS and protein antigens on the surface of the bacterium. In this review, we describe well-studied targets of anti-pneumococcal antibodies and describe antibody functions and effectiveness against S. pneumoniae.